Differential phosphorylation of NMDAR1–CaMKII–MAPKs in the rat nucleus accumbens following chronic ethanol exposure. (15th June 2015) - Zhao, Bin; Wang, YunPeng; Li, Yunxiao; Qiao, Xiaomeng; Yan, Peng; Zhu, Yongsheng; Lai, Jianghua
Highlights: Ethanol intake increases locomotor and reduced anxiety-like behavior in rats. NMDAR1 phosphorylation was inhibited by chronic ethanol in the accumbens. Ethanol withdrawal increases NMDAR1 and CaMKII phosphorylation in the accumbens. NMDAR1–CaMKII–ERK signaling was more pronounced in the accumbens shell than in the core. Abstract: Previous studies suggest that the nucleus accumbens shell (AcbSh) and core (AcbC) regions may have distinct roles in ethanol consumption. N -Methyl-d -aspartate receptor 1 (NMDAR1), Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and extracellular signal-regulated kinases (ERKs) have been demonstrated to contribute to and possibly interact in the molecular mechanism underlying ethanol dependence and relapse. However, little is known regarding the mechanisms underlying the effects of ethanol exposure, withdrawal, and re-exposure, particularly with regard to NMDAR1–CaMKII–ERK signaling in accumbens subregions. In the present study, rats were provided with a 6% ethanol solution as their only drinking source. We found that ethanol exerted locomotor stimulant and anxiolytic effects in open field behaviors. Phosphorylation of NMDAR1, CaMKII and ERK was significantly decreased in the AcbSh and AcbC following chronic ethanol exposure. Ethanol withdrawal increased phospho-NMDAR1 and phospho-CaMKII expression in the AcbSh. Ethanol withdrawal also induced an increase of phospho-ERK1/2 in both the AcbSh and AcbC, while ethanol re-exposure decreased phospho-ERK in the AcbSh. These results indicated that the activation of NMDAR1–CaMKII–ERK signaling in the AcbSh but not the AcbC would contribute more to ethanol drinking and chronic ethanol-related negative emotional states.